How to Report Pesticide Misuse in Florida - Frederick M. Fishel (EDIS, 2012)
Pesticides provide benefits in many facets of daily life, including protecting food production and health, enhancing our recreational areas, maintaining our rights-of-way, and protecting wildlife, aquatic sites, and natural areas. However, misuse does occur and those who are negligent must take responsibility for their actions. This 3-page fact sheet was written by F. M. Fishel and published by the UF Department of Agronomy, October 2012.